2020
DOI: 10.1001/jamanetworkopen.2020.23282
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Prior Psychiatric Diagnosis With Mortality Among Hospitalized Patients With Coronavirus Disease 2019 (COVID-19) Infection

Abstract: had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 6 publications
10
122
3
2
Order By: Relevance
“…These people are also at increased risk for COVID‐19 complications, as reflected in higher rates of hospitalization and death 4 . Other recent studies 5,6 have confirmed these data.…”
supporting
confidence: 75%
“…These people are also at increased risk for COVID‐19 complications, as reflected in higher rates of hospitalization and death 4 . Other recent studies 5,6 have confirmed these data.…”
supporting
confidence: 75%
“…Similarly, a large US based study examined the relationship between existing psychiatric disorders and risk for COVID-19 across 54 health care organizations and found that among patients with existing psychiatric disorders, risk for testing positive for COVID-19 was 1.65 times higher compared to those without existing psychiatric disorders ( Taquet et al., 2020 ). In addition to increased risk of testing positive for COVID-19 and increased risk for hospitalization, recent evidence out of five hospitals in the Northeast region of the US also showed that among those who tested positive for COVID-19 with existing mental health disorders also had an increased risk for mortality compared to those who tested positive for COVID-19 and did not have an existing mental health disorder ( Li et al., 2020 ). Given the small sample size in the current study for individuals with a mental health diagnosis, further investigation is needed to understand the risk of infection that individuals with a mental health diagnosis have as well as risk for hospitalization and mortality among positive screens.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this hypothesis was formulated based on the initial data regarding the evolution of the pandemic in psychiatry [ [1] , [2] ],[ 22 ]. Some recent results, however, suggest that suffering from a psychiatric disorder could increase the risk of being affected by COVID-19 [ 23 ], of developing a severe form of it [ 1 ], or even of dying as a result of it [ 24 ], while psychotropic drugs may increase COVID-19 mortality in elderly patients [ 25 ],. These data encouraged us to make assumptions about what could have constituted a possible initial prophylactic factor in psychiatry settings.…”
Section: Pharmacochemical Based Hypothesismentioning
confidence: 99%